Are Standard Doses of Renally-Excreted Antiretrovirals in Older Patients Appropriate: A PBPK Study Comparing Exposures in the Elderly Population With Those in Renal Impairment - M. De Sousa Mendes; Manoranjenni Chetty (Adis, Springer Healthcare, 2019)
Abstract Background and Objectives The elderly population receives the majority of prescription drugs but are usually excluded from Phase 1 clinical trials. Alternative approaches to estimate increases in toxicity risk or decreases in efficacy are therefore needed. This study predicted the pharmacokinetics (PK) of three renally excreted antiretroviral drugs in the elderly population and compared them with known exposures in renal impairment, to evaluate the need for dosing adjustments. Methods The performance of the physiologically based pharmacokinetic (PBPK) models for tenofovir, lamivudine and emtricitabine were verified using clinical data in young and older subjects. Models were then used to predict PK profiles in a virtual population aged 20 to 49 years (young) and a geriatric population aged 65 to 74 years (elderly). Predicted exposure in the elderly was then compared with exposure reported for different degrees of renal impairment, where doses have been defined. Results An increase in exposure (AUC) with advancing age was predicted for all drugs. The mean ratio of the increase in exposure were 1.40 for emtricitabine, 1.42 for lamivudine and 1.48 for tenofovir. The majority of virtual patients had exposures that did not require dosage adjustments. About 22% of patients on tenofovir showed exposures similar to that in moderate renal impairment, where dosage reduction may be required. Conclusion Comparison of the exposure in the elderly with exposure observed in patients with different levels of renal impairment, indicated that a dosage adjustment may not be required in elderly patients on lamivudine, emtricitabine and the majority of the patients on tenofovir. Clinical trials to verify these predictions are essential.